2021
DOI: 10.1111/ctr.14462
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of the homologous kidney allograft in simultaneous pancreas‐kidney transplants and its potential protective role

Abstract: The superior death-censored graft survival of the pancreas allograft in simultaneous pancreas kidney transplants (SPK) over pancreas alone transplants (PTA) has long been recognized. Using data from the Scientific Registry of Transplant Recipients (SRTR) and a high-volume pancreas transplant program, we investigated the possible protective role of the kidney allograft in SPK transplants. We analyzed 19 043 primary pancreas transplants between 2000 and 2020, including 735 transplants performed at the University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…There was a study by O.K. Serrano et al in literature that reported on a possible role of homologous kidney graft on pancreas allograft 21 . Similar to our results, they showed that SPLK performance in terms of the pancreas graft survival was inferior to that of SPK owing to the possible protective role of homologous kidney graft on pancreas allograft when they were from the same donors as in SPK.…”
Section: Discussionmentioning
confidence: 99%
“…There was a study by O.K. Serrano et al in literature that reported on a possible role of homologous kidney graft on pancreas allograft 21 . Similar to our results, they showed that SPLK performance in terms of the pancreas graft survival was inferior to that of SPK owing to the possible protective role of homologous kidney graft on pancreas allograft when they were from the same donors as in SPK.…”
Section: Discussionmentioning
confidence: 99%